Tales of Change: Public Administration Reform and Narrative Mode - Sköldberg, Kaj (Organization Science, 1994)
Several institutional theorists have noted the existence of inconsistencies and decouplings in organizations, depending on conflicting signals from the milieu. Others have pointed out the pressure for homogeneity in organizational fields. These positions may seem contradictory, yet the present article gives support to both of them. The empirical basis is a series of case studies of change in Swedish local authorities. Faced with conflicting signals from the outside, and lacking an internal, dominating center, the organizations showed similar patterns of inconsistencies and decouplings. Problems, power, and symbols, which constituted the foci of the study, all manifested a common deep structure. It combined two radically opposed narrative conventions, tragedy and romantic comedy. The result was a third, and incoherent convention—fragmented satire. At a higher degree of resolution, even single genres within the three main conventions emerged in the analysis. The narrative conventions and their genres, rather than more substantial concerns, formed the texture of the changes, virtually disengaging the latter from mundane realities.